THE ROLE OF GAME-BASED TECHNOLOGIES IN DEVELOPING BASIC ENGLISH LANGUAGE COMPETENCIES - Shamsuddinova Diyoraxon Yorqinbek qizi; Sayfulloyeva Nilufar Zexniddin qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Game-based technologies have emerged as transformative tools in the domain of language education, particularly in enhancing basic English language competencies. This article explores the significance of incorporating game-based learning approaches into English language teaching, emphasizing their impact on motivation, engagement, and skill acquisition. By leveraging interactive and immersive environments, educators can  create  dynamic  learning  experiences  that  cater  to  diverse  learning  styles  and linguistic  backgrounds.  The  findings  underscore  the  necessity  of  integrating  these technologies into curricula to foster language proficiency and critical thinking among learners.